2010
DOI: 10.2176/nmc.50.1051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age and Anti-platelet/Anti-coagulant Use on the Outcome of Elderly Patients With Fall-Related Traumatic Intracranial Hemorrhage

Abstract: Ground-level fall is the most common cause of traumatic intracranial hemorrhage (TICH) in the elderly. Many studies on geriatric TICH have regarded patients aged AE65 years as a single group, but substantial heterogeneity is likely to exist within this population. Eighty-two elderly patients with fall-related TICH treated in our institution during a 6-year period were stratified into 3 age groups (65-74, 75-84, and AE85 years), and intergroup differences in the demographics and outcomes at discharge were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“… 38 , 39) Although there are a few reports that neither anticoagulant nor antiplatelet influence on the mortality and morbidity in patients with TBI, 40 42) most of the available data suggest that a pre-injury reception of either anticoagulant or antiplatelet agent increases the risk of poor outcome in patients with TBI, mainly resulting from larger or repeated intracranial hematoma. 43 – 52) It has been also reported that the history of anticoagulant is closely associated with the occurrence of talk and deteriorate. 53) …”
Section: Clinical Characteristics and Problems Of Tbi In The Elderlymentioning
confidence: 99%
“… 38 , 39) Although there are a few reports that neither anticoagulant nor antiplatelet influence on the mortality and morbidity in patients with TBI, 40 42) most of the available data suggest that a pre-injury reception of either anticoagulant or antiplatelet agent increases the risk of poor outcome in patients with TBI, mainly resulting from larger or repeated intracranial hematoma. 43 – 52) It has been also reported that the history of anticoagulant is closely associated with the occurrence of talk and deteriorate. 53) …”
Section: Clinical Characteristics and Problems Of Tbi In The Elderlymentioning
confidence: 99%
“…This might be explained in that the preoperative protocol dictates that an elevated international normalized ratio (INR) due to warfarin is to be treated and normalized before surgery is performed (8). The role of anticoagulation medicine in outcome after intracranial hemorrhage is still debated with some investigators (6) arguing that it does not have an adverse effect on outcome and some (12,20) stating the opposite.…”
Section: Surgically Treated Patientsmentioning
confidence: 99%
“…The authors unfortunately did not specifically mention which agents were consumed by the subjects. This study found that poor Glasgow Outcome Scale (GOS) was more common in the oldest subgroup (≥ 85 yo), despite not statistically significant (p = 0.37) (Inamasu, J. 2010).…”
Section: Anticoagulants and Risk Of Traumatic Intracranial Hemorrhagementioning
confidence: 63%